Creatine Supplementation in Sport and Medicine: Efficacy, Safety, and Therapeutic Potential in the Light of Current Scientific Evidence - Wnęk, Agata; Biskup , Alicja; Gniewkiewicz, Aleksandra; Turzyńska, Paulina; Hucała, Zuzanna; Jankowska, Natasza (Quality in Sport, 2026)
Creatine is a naturally occurring compound stored mainly in skeletal muscles, where it plays an essential role in energy production during high-intensity exercise. Creatine monohydrate is one of the most widely studied and effective ergogenic supplements, shown to improve strength, anaerobic performance, muscle mass, and recovery. This paper reviews the current evidence on the effectiveness, safety, and applications of creatine supplementation in sports and health. In addition to its well-established benefits for athletic performance, emerging research suggests potential roles in neuroprotection, healthy aging, and rehabilitation. Current evidence indicates that creatine monohydrate is safe for both short- and long-term use when consumed according to recommended guidelines.